Examining changes in pain interference via pandemic-induced isolation among patients receiving medication for opioid use disorder: a secondary data analysis - Frohe, Tessa; Janssen, Tim; Garner, Bryan R.; Becker, Sara J. (BMC public health, 2024)
Background Early in the pandemic, the United States population experienced a sharp rise in the prevalence rates of opioid use, social isolation, and pain interference. Given the high rates of pain reported by patients on medication for opioid use disorder (MOUD), the pandemic presented a unique opportunity to disentangle the relationship between opioid use, pain, and social isolation in this high-risk population. We tested the hypothesis that pandemic-induced isolation would partially mediate change in pain interference levels experienced by patients on MOUD, even when controlling for baseline opioid use. Such work can inform the development of targeted interventions for a vulnerable, underserved population. Methods Analyses used data from a cluster randomized trial ( N = 188) of patients on MOUD across eight opioid treatment programs. As part of the parent trial, participants provided pre-pandemic data on pain interference, opioid use, and socio-demographic variables. Research staff re-contacted participants between May and June 2020 and 133 participants (71% response rate) consented to complete a supplemental survey that assessed pandemic-induced isolation. Participants then completed a follow-up interview during the pandemic that again assessed pain interference and opioid use. A path model assessed whether pre-pandemic pain interference had an indirect effect on pain interference during the pandemic via pandemic-induced isolation. Results Consistent with hypotheses, we found evidence that pandemic-induced isolation partially mediated change in pain interference levels among MOUD patients during the pandemic. Higher levels of pre-pandemic pain interference and opioid use were both significantly associated with higher levels of pandemic-induced isolation. In addition, pre-pandemic pain interference was significantly related to levels of pain interference during the pandemic, and these pain levels were partially explained by the level of pandemic-induced isolation reported. Conclusions Patients on MOUD with higher use of opioids and higher rates of pain pre-pandemic were more likely to report feeling isolated during COVID-related social distancing and this, in turn, partially explained changes in levels of pain interference. These results highlight social isolation as a key risk factor for patients on MOUD and suggest that interventions promoting social connection could be associated with reduced pain interference, which in turn could improve patient quality of life. Trial registration NCT03931174 (Registered 04/30/2019).